Minding Damasio - Emilia Barile (Ledizioni, 2016)
Despite unanimous recognition in the field of neuroscience, where the name of Damasio is inextricably linked to the discovery of the somatic marker, he didn't achieve the same success with the public of philosophers, though he loved and hated some of them in particular. These were the giants on whose shoulders he knew he had to stand, in order to look beyond the disciplinary boundaries that are always too strict for every kind of research, but even more so for the research on the mystery of the sentient and thinking body we ourselves are. Here is what I know about him, he who has the charm of a storyteller even with his unbearable faults. This and something else Damasio gives to the reader dissatisfied by the philosophical or the available psychological theories' explanations, all the while avoiding running into the traps induced by another, no less detrimental, dualism: the neuroscientific dualism between body and brain. This is another of the -isms Damasio contributed to refute, challenging a real contemporary 'mystique of the brain'.